Forming Excellent Teachers: Integration of Social Competence and Makārim Al-Sharī'ah Ethics in Madrasahs - Dian Namora; Syahraini Tambak; Najmi Hayati; Yenni Yunita; Daharmi Astuti (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2025)
This research aims to construct how the integration of social competence and ethics of Makārim Al-Syarī'ah can form excellent teachers in the environment at MAN 2 Pekanbaru City. This research uses a qualitative approach with phenomenological methods. The informants in this study amounted to three people, namely the head of curriculum, PAI teacher, and head of student affairs, who were selected using purposive sampling technique. Data were collected through in-depth interviews, observation, and documentation. The data analysis techniques used were data reduction, data presentation, and conclusion drawing. The research shows that the ethics of Makārim Al-Syarī’ah can be integrated into social competence to form superior teachers and become a strong foundation for madrasah teachers in developing interaction skills that are oriented towards creating benefits. Although, some teachers still have a basic understanding and have not received adequate training related to the integration of Makārim Al-Syarī’ah ethics in social competence. The head of curriculum proposed that the ethical values of Makārim Al-Syarī’ah become part of the teacher's personality to improve competence in interaction. The PAI teacher emphasized the importance of good communication with parents to create effective collaboration in solving student problems. The head of student affairs emphasized that the ethics of Makārim Al-Syarī’ah includes spiritual values, norms, and emotional values that must be applied in learning. The study recommends a regular training program for teachers on the application of Makārim Al-Syarī’ah ethics in teaching practice, creating a structured communication guide between teachers and parents, and establishing a periodic evaluation system to ensure teachers play their role as effective role models in shaping student character.Keywords: Excellent Teacher, teacher professionalism, Makarim Al-syari'ah